2022
DOI: 10.3389/fimmu.2022.850494
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Analysis of Nasal Polyps Reveals a More Pronounced Type 2 Transcriptomic Profile of Epithelial Cells and Mast Cells in Aspirin-Exacerbated Respiratory Disease

Abstract: Chronic rhinosinusitis with nasal polyps is affecting up to 3% of Western populations. About 10% of patients with nasal polyps also suffer from asthma and intolerance to aspirin, a syndrome called aspirin-exacerbated respiratory disease. Although eosinophilic inflammation is predominant in polyps of both diseases, phenotypic differences in the tissue-derived microenvironment, elucidating disease-specific characteristics, have not yet been identified. We sought to obtain detailed information about phenotypic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
16
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 58 publications
(83 reference statements)
5
16
2
Order By: Relevance
“…Patients suffering from CRSwNP or N-ERD, and therefore suffering from polyps, showed severely impaired olfactory performance as assessed by the Sniffin' Sticks test and diseasesspecific quality of life as determined by SNOT-22. The associated significantly higher levels of IL-5 and Eotaxin-3 in nasal mucosal lining fluids are characteristic of the pronounced type 2 endotype in these patient groups (14,33). Though a role for the nasal microbiome in olfactory function has been suggested (18, 34), we did not observe any association of the smell performance as assessed by TDI score with nasal microbiome composition.…”
Section: Discussioncontrasting
confidence: 52%
“…Patients suffering from CRSwNP or N-ERD, and therefore suffering from polyps, showed severely impaired olfactory performance as assessed by the Sniffin' Sticks test and diseasesspecific quality of life as determined by SNOT-22. The associated significantly higher levels of IL-5 and Eotaxin-3 in nasal mucosal lining fluids are characteristic of the pronounced type 2 endotype in these patient groups (14,33). Though a role for the nasal microbiome in olfactory function has been suggested (18, 34), we did not observe any association of the smell performance as assessed by TDI score with nasal microbiome composition.…”
Section: Discussioncontrasting
confidence: 52%
“…Experiments showed that upregulation of OIP5-AS1 was closely related to the acceleration of cell apoptosis and the inflammatory response [ 71 , 72 ]. NEAT1 is widely expressed in mammalian cell types, and is overexpressed in several inflammation-related disorders [ 73 , 74 ]. In the acute kidney injury mouse model, KCNQ1OT1 was highly expressed, and knockdown of the KCNQ1OT1 promoted cell proliferation and prevented apoptosis and inflammation [ 75 ].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically among DEGs detected in EoD compared to controls, within CD4 + T there was an upregulation of genes associated with the chronic rhinosinusitis and nasal polyps ( SCGB3A1 and MTRNR2L8 ) (61, 62), and downregulation of IL27RA , whose decreased expression is associated with allergic airway inflammation (63). Within DC cells, there was also dysregulation of genes associated with chronic obstructive pulmonary disorder (COPD) ( LILRA5, IGLC2 , and IGLC3 ) (64, 65).…”
Section: Discussionmentioning
confidence: 99%